The Role of Resilience on Employee Performance in Various Organizational Sectors: A Scoping Review - Agung Wicaksono; Deni Agung Wicaksono; Endang Erna Wati; Faza Ardini; Mutiara Vinanda; Stanike Marsella; Fatchiah E. Kertamuda (Yayasan Sembilan Pemuda Indonesia, 2027)
This scoping review aims to map empirical evidence regarding the role of psychological resilience in employee performance across various organizational sectors. Employing the Arksey & O’Malley framework alongside PRISMA guidelines, a systematic literature search was conducted on Google Scholar and ScienceDirect databases covering the 2020–2026 period, yielding 7 final articles from 552 initial records for descriptive analysis. The synthesis consistently demonstrates that psychological resilience significantly enhances job performance, adaptive performance, service quality, thriving at work, and work engagement, while reducing turnover intention. These relationships are mediated by factors such as transformational leadership, belief restoration, and employee exploration, and moderated by perceived risk and challenge stressors. This review uniquely offers a cross-sectoral synthesis, positioning resilience not merely as an individual personal resource but as a strategic organizational asset, while integrating emerging evidence on AI-driven HR practices in its development. Organizations are advised to implement resilience-building interventions, foster supportive work climates, and adopt adaptive HR practices to sustain productivity amid uncertainty. Theoretically, this review enriches Job Demands-Resources Theory by confirming resilience as a personal resource that buffers job demands and fuels motivational pathways to optimal performance, providing actionable insights for HR practitioners and organizational leaders seeking evidence-based strategies for workforce sustainability.